1995
DOI: 10.1128/mcb.15.7.3672
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Activates Serum Response Factor-Dependent Transcription By A Ras- and Elk-1-Independent Mechanism That Involves a Ca2+/Calmodulin-Dependent Kinase

Abstract: Enhanced levels of cytoplasmic Ca2+ due to membrane depolarization with elevated levels of KCl or exposure to the Ca2+ ionophore ionomycin stimulate serum response element (SRE)-dependent transcription in the pheochromocytoma cell line PC12. By using altered binding specificity mutants of transcription factors that bind to the SRE, it was demonstrated that in contrast to treatment with purified growth factors, such as nerve growth factor, the serum response factor (SRF), but not Elk-1, mediates Ca(2+)-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
181
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(190 citation statements)
references
References 60 publications
7
181
1
Order By: Relevance
“…In many studies, the K-ras gene has been proven to take part in cell growth regulation by activating MAP kinase to activate transcription factor ELK-1 (Marais et al, 1993;Miranti et al, 1995). In 1996, Xing et al found that introduction of activated ras oncogene into PC12 cells regulated gene expression by activating RAF and MAP kinase and then RSK2 of pp90RSK family to phosphorylate CREB (Xing et al, 1996;Cesare et al, 1998;Beaupre et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, the K-ras gene has been proven to take part in cell growth regulation by activating MAP kinase to activate transcription factor ELK-1 (Marais et al, 1993;Miranti et al, 1995). In 1996, Xing et al found that introduction of activated ras oncogene into PC12 cells regulated gene expression by activating RAF and MAP kinase and then RSK2 of pp90RSK family to phosphorylate CREB (Xing et al, 1996;Cesare et al, 1998;Beaupre et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The direct mechanism of Rho induction of the SRE is unclear, however it was recently found that Rho and LIM kinase control of actin treadmilling and the control of free actin concentrations in the cells was critical for Rho and LIM kinase activation of the SRE (Sotiropoulos et al, 1999). In an additional pathway, increased calcium concentrations can also activate the SRE independently of the TCF site through a CaMK dependent pathway (Miranti et al, 1995). Since CaMK can also activate CREB, it is possible that the FAP1 site may also mediate calcium induction of the c-fos enhancer along with the SRE.…”
Section: Discussionmentioning
confidence: 99%
“…In T lymphocytes, the activation of nuclear factor of activated T cells (NF-AT) is quantitatively correlated with the intracellular concentration of Ca 2+ (Negulescu et al, 1994). The inÂŻux of Ca 2+ through voltage-sensitive Ca 2+ channels also stimulates serum response factor (SRF)-dependent transcription in the pheochromocytoma cell line PC12 (Miranti et al, 1995). Sequencing of the 5'ÂŻanking region of the mouse MKP-1 gene revealed the presence of several consensus sequences that include one CRE, two SP1 sites, two CTF/NF1-like sites, and one E-box motif (Noguchi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%